Inhibition of cell proliferation, invasion and migration by the cardenolides digitoxigenin monodigitoxoside and convallatoxin in human lung cancer cell line. Issue 11 (2nd June 2016) - Schneider, Naira F. Z.; Geller, Fabiana C.; Persich, Lara; Marostica, Lucas L.; Pádua, Rodrigo M.; Kreis, Wolfgang; Braga, Fernão C.; Simões, Cláudia M. O.
Abstract: Cardiac glycosides consist of a large family of naturally derived compounds that are clinically used to treat congestive heart failure, and also present anticancer properties. In this study, the cytotoxic effects of two cardenolides, digitoxigenin monodigitoxoside (DGX) and convallatoxin (CON) were screened in four human tumour cell lines. Both compounds showed anti-proliferative effects in all tumour cells, at nanomolar concentrations. Since the human lung cancer cell line A549 was the most sensitive, we investigated the anti-proliferative, anti-migratory and anti-invasive effects of these cardenolides. DGX and CON reduced A549 cell migration, being able to reduce more than 90% of cell invasion. Their effects on the expression of key regulators of metastatic mechanism showed decreased levels of MMP-2, MMP-9 and p-FAK. Both compounds also presented low toxicity for healthy cells. Finally, this work provides the first insights into the effects of these cardenolides on key steps of lung cancer metastasis. Graphical Abstract: